Mark 2.15 in Even Broader Context: A Reflection - Malbon, Elizabeth Struthers (Journal for the study of the New Testament, 2026)
My original article on the referent of "his house" in Mark 2.15 was published in 1985 as "TH OIKIA AYTOY: Mark 2.15 in Context" in NTS 31: 282-92. This brief essay is both a look back to that short article and its original context and a look forward to where I went from there and to this present volume. That is, this reflection is putting Mk 2.15 into an even broader context. My own research trajectory was from Lévi-Straussian structuralism to narrative criticism and from narrative space to narrative characterization. The consistent thread has been appreciating relationships - and relationships between relationships: how parts relate within the whole, how individual elements of Mark's narrative contribute to its overall meaning, and how that overall meaning is tensive, challenging, surprising, and open-ended.